Detection of Salmonella spp. Contamination in Chicken Meat Samples Using the SNI ISO 6579-1:2017 Method: Application of Standard Microbiological Detection Procedures in Poultry Meat Testing - Vika Aulia Royani; Dzulfikar Yusuf Priyanatha Priyanatha; Justin S Sitorus Sitorus; Ngakan Putu Agung Dharma Pratama Pratama; Annisa Nur Adhiak Adhiak; Ni’matul Aliyah Aliyah; Hendri Busman Busman; Priyambodo Priyambodo; Ahmad Ikhsanudin Ikhsanudin; Jani Master Master (Jurnal Biogenerasi, 2026)
Salmonella spp. is a pathogenic bacterium responsible for foodborne diseases and is commonly found in poultry products, particularly chicken meat. This study aimed to detect and identify Salmonella spp. contamination in chicken meat samples tested at the Veterinary Public Health Laboratory (Kesmavet) DKI Jakarta and to evaluate the results as a basis for food safety assessment. The examination was conducted using a standardized microbiological method based on SNI ISO 6579-1:2017, which includes pre-enrichment, selective enrichment, isolation on selective media, biochemical testing, and serological confirmation using polyvalent O and H antisera. Identification was determined based on specific agglutination reactions between bacterial antigens and antisera. The results demonstrated that the applied procedure was able to accurately detect the presence of Salmonella spp. in accordance with laboratory standards. Routine microbiological surveillance is essential to control contamination risks and improve the safety of animal-derived food products in order to protect public health.